Teacher wellbeing within the context of educational psychology casework for children and young people with SEND: an exploration of the experiences, perceptions and practices of educational psychologists - Akyeampong-Spencer, Afia (2021)
Research (e.g. by Zafeiriou & Gulliford, 2020) indicates that teaching staff supporting children with Special Educational Needs and Disabilities (SEND) might present with issues related to their well-being within the context of educational psychology casework. The present study therefore uniquely explored the practices, perceptions and experiences of educational psychologists (EPs) in relation to teacher well-being (TWB) in the context of educational psychology casework for children and young people (CYP) with SEND. Semi-structured interviews were used with six EPs to explore their practices and experiences, drawing additionally on vignette methodology to explore their beliefs in this area. Thematic analysis, used on interview data, suggests that EPs encounter TWB issues within casework across all areas of SEND, linking not only to the case demands, but to stressors within teachers’ personal lives and within the profession. The data indicates that TWB needs can interrupt EPs’ ability to problem-solve, impacting on their experience of the casework outcomes and trajectory. The data also tentatively suggests that support for TWB might be a secondary outcome of educational psychology casework. Indeed, some EPs reflected their use of strategies to support both teachers’ professional and affective well-being (as defined by van Horn et al., 2004) within casework. They also highlighted some constraints and professional duties which impede on their responses to TWB needs in casework, including those of service delivery and time. Helpfully, EPs reflected some of their responses which may enable TWB needs to be met within their casework involvement despite such constraints. Vignette methodology indicated considerable overlap between EPs’ beliefs and their accounts of their own responses to TWB needs in casework. The findings suggest that EPs should consider teachers’ potential fragility within casework and consider using the casework context as a vehicle for TWB support to find a way forward for the CYP at the heart of this fundamental aspect of EPs’ practice.